Modernism in a global context - Kalliney, Peter J., 1971- (New modernisms series., 2016)
Exploring the transnational dimension of literary modernism and its increasing centrality to our understanding of 20th-century literary culture, Modernism in a Global Context surveys the key issues and debates central to the 'global turn' in contemporary Modernist Studies. Topics covered include: - Transnational exchanges between Western and non-Western literary cultures - Imperialism and the Modernism - Cosmopolitanism and postcolonial literatures - Global literary institutions - from the Little Magazine to the Nobel Prize - Mass media - photography, cinema, and radio broadcasting in the modernist age Exploring the work of writers such as T.S. Eliot, Virginia Woolf, Jean Rhys, Wole Soyinka, Salman Rushdie and critics such as Edward Said, Pascale Casanova, Paul Gilroy, and Gayatri Spivak amongst many others, the book also includes a comprehensive annotated guide to further reading and online resources.